A Causality Relationship Between Tax Revenue and Government Expenditure In Indonesia - Sriyana, Jaka (Economic Journal of Emerging Markets, 2011)
This paper attempts to model the relationship between tax revenue and government expenditure for Indonesia over the period 1970-2007. The empirical analysis employs tests of cointegration and Vector Error Correction Model (VECM). The empirical evidence suggests that there is a long run relationship between tax and government expenditure, but in the short term, the model explains unidirectional causality relationship, namely from tax revenue to govern ment expenditure This finding indicates that the budget deficit increase continuously, which threaten the fiscal sustainability in the long term. It suggests that the government should organize a better management on public finance policies to support the tax-spend fiscal policy. Key words: tax, government, causality, expenditure, cointegration.